The labor market effects of trade unions: Layard meets Melitz - Marco De Pinto; Jochen Michaelis (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Trade unions are typically able to convert their industrial power into political power. We show that, depending on the parameter constellation, stronger trade unions may be welfare-improving in terms of an increase in aggregate employment and output, if they successfully lobby for lower trade barriers set by the government.
Keywords: F13; F16; J51; 330; Trade unions; lobbying; trade liberalization